2021
DOI: 10.1158/1078-0432.ccr-21-2484
|View full text |Cite
|
Sign up to set email alerts
|

Extrachromosomal DNA in HPV-Mediated Oropharyngeal Cancer Drives Diverse Oncogene Transcription

Abstract: Purpose: Human papillomavirus (HPV) plays a major role in oncogenesis and circular extrachromosomal DNA (ecDNA) is found in many cancers. However, the relationship between HPV and circular ecDNA in human cancer is not understood. Experimental Design: Forty-four primary tumor tissue samples were obtained from a cohort of patients with HPV-positive oropharynx squamous cell carcinoma (OPSCC). Twenty-eight additional HPV orophary… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 62 publications
0
43
0
Order By: Relevance
“…MIDS also includes mimicry between microbial and cancer antigens. [156,157] Should genetic cargo be shared between intracellular bacteria and host cells, as biotechnology already shows is possible [24] and cancer virology affirms, [45,46] MIDS must account for DNA and RNA from multiple species.…”
Section: Implications and Hypotheses If Cancer Clonality Is Multispeciesmentioning
confidence: 99%
“…MIDS also includes mimicry between microbial and cancer antigens. [156,157] Should genetic cargo be shared between intracellular bacteria and host cells, as biotechnology already shows is possible [24] and cancer virology affirms, [45,46] MIDS must account for DNA and RNA from multiple species.…”
Section: Implications and Hypotheses If Cancer Clonality Is Multispeciesmentioning
confidence: 99%
“…Recently, Pang et al revealed that ecDNA was present in nearly all HPVOPCs. Additionally, a novel human-viral hybrid ecDNA was also identified in HPVOPC [86]. Moreover, hybrid ecDNA highly expresses fusion transcripts that contain promoter and oncogene sequences of HPV.…”
Section: Ecdna In Hpv-mediated Oropharyngeal Cancermentioning
confidence: 99%
“…These fusion transcripts are associated with downstream human transcripts. These downstream transcripts could drive carcinogenesis and immune evasion [86]. Viral promoters and genes account for the high expression of hybrid transcripts and human oncogenes in hybrid ecDNA structures, which is facilitated by high levels of chromatin modifications (such as H3K27 ac) in ecDNA [11,86].…”
Section: Ecdna In Hpv-mediated Oropharyngeal Cancermentioning
confidence: 99%
“…Hybrid human–virus extra chromosomal DNA (ecDNA) was shown to induce an increase in HPV oncogenes E6 and E7 copy number. More recently, the interaction of the HPV genome with cancer‐associated ecDNA was shown to induce high expression of hybrid viral–human oncogene transcripts in OPSCC [24] .…”
Section: Introductionmentioning
confidence: 99%